Direct C–H trifluoromethylation of di- and trisubstituted alkenes by photoredox catalysis - Tomita, Ren; Yasu, Yusuke; Koike, Takashi; Akita, Munetaka (Beilstein Journal of Organic Chemistry, 2014)
Background: Trifluoromethylated alkene scaffolds are known as useful structural motifs in pharmaceuticals and agrochemicals as well as functional organic materials. But reported synthetic methods usually require multiple synthetic steps and/or exhibit limitation with respect to access to tri- and tetrasubstituted CF3-alkenes. Thus development of new methodologies for facile construction of Calkenyl–CF3 bonds is highly demanded.Results: The photoredox reaction of alkenes with 5-(trifluoromethyl)dibenzo[b,d]thiophenium tetrafluoroborate, Umemoto’s reagent, as a CF3 source in the presence of [Ru(bpy)3]2+ catalyst (bpy = 2,2’-bipyridine) under visible light irradiation without any additive afforded CF3-substituted alkenes via direct Calkenyl–H trifluoromethylation. 1,1-Di- and trisubstituted alkenes were applicable to this photocatalytic system, providing the corresponding multisubstituted CF3-alkenes. In addition, use of an excess amount of the CF3 source induced double C–H trifluoromethylation to afford geminal bis(trifluoromethyl)alkenes.Conclusion: A range of multisubstituted CF3-alkenes are easily accessible by photoredox-catalyzed direct C–H trifluoromethylation of alkenes under mild reaction conditions. In particular, trifluoromethylation of triphenylethene derivatives, from which synthetically valuable tetrasubstituted CF3-alkenes are obtained, have never been reported so far. Remarkably, the present facile and straightforward protocol is extended to double trifluoromethylation of alkenes.
Keywords: electrophilic trifluoromethylating reagent; multi-substituted alkene; photoredox catalysis; radical reaction; trifluoromethylation

Organofluorine Compounds: Chemistry and Applications - Hiyama, T. (Springer, 2000)

Fluorine in Medicinal Chemistry and Chemical Biology - Ojima, I. (Wiley-Blackwell, 2009)

(untitled) - Shimizu, M.; Hiyama, T. (Angew. Chem., Int. Ed., 2005)

(untitled) - Ma, J.-A.; Cahard, D. (J. Fluorine Chem., 2007)

(untitled) - Shibata, N.; Mizuta, S.; Toru, T. (J. Synth. Org. Chem., Jpn., 2008)

(untitled) - Ma, J.-A.; Cahard, D. (Chem. Rev., 2008)

(untitled) - Tomashenko, O. A.; Grushin, V. V. (Chem. Rev., 2011)

(untitled) - Furuya, T.; Kamlet, A. S.; Ritter, T. (Nature, 2011)

(untitled) - Amii, H. (J. Synth. Org. Chem., Jpn., 2011)

(untitled) - Studer, A. (Angew. Chem., Int. Ed., 2012)

(untitled) - Macé, Y.; Magnier, E. (Eur. J. Org. Chem., 2012)

(untitled) - Liang, T.; Neumann, C. N.; Ritter, T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Yoon, T. P.; Ischay, M. A.; Du, J. (Nat. Chem., 2010)

(untitled) - Narayanam, J. M. R.; Stephenson, C. R. J. (Chem. Soc. Rev., 2011)

(untitled) - Teplý, F. (Collect. Czech. Chem. Commun., 2011)

(untitled) - Tucker, J. W.; Stephenson, C. R. J. (J. Org. Chem., 2012)

(untitled) - Xuan, J.; Xiao, W.-J. (Angew. Chem., Int. Ed., 2012)

(untitled) - Maity, S.; Zheng, N. (Synlett, 2012)

(untitled) - Shi, L.; Xia, W. (Chem. Soc. Rev., 2012)

(untitled) - Xi, Y.; Yi, H.; Lei, A. (Org. Biomol. Chem., 2013)

(untitled) - Hari, D. P.; König, B. (Angew. Chem., Int. Ed., 2013)

(untitled) - Prier, C. K.; Rankic, D. A.; MacMillan, D. W. C. (Chem. Rev., 2013)

(untitled) - Reckenthäler, M.; Griesbeck, A. G. (Adv. Synth. Catal., 2013)

(untitled) - Nagib, D. A.; MacMillan, D. W. C. (Nature, 2011)

(untitled) - Nguyen, J. D.; Tucker, J. W.; Konieczynska, M. D.; Stephenson, C. R. J. (J. Am. Chem. Soc., 2011)

(untitled) - Ye, Y.; Sanford, M. S. (J. Am. Chem. Soc., 2012)

(untitled) - Mizuta, S.; Verhoog, S.; Engle, K. M.; Khotavivattana, T.; O’Duill, M.; Wheelhouse, K.; Rassias, G.; Médebielle, M.; Gourverneur, V. (J. Am. Chem. Soc., 2013)

(untitled) - Kim, E.; Choi, S.; Kim, H.; Cho, E. J. (Chem.–Eur. J., 2013)

(untitled) - Wilger, D. J.; Gesmundo, N. J.; Nicewicz, D. A. (Chem. Sci., 2013)

(untitled) - Jiang, H.; Cheng, Y.; Zhang, Y.; Yu, S. (Eur. J. Org. Chem., 2013)

(untitled) - Xu, P.; Xie, J.; Xue, Q.; Pan, C.; Cheng, Y.; Zhu, C. (Chem.–Eur. J., 2013)

(untitled) - Koike, T.; Akita, M. (Top. Catal., 2014)

(untitled) - Umemoto, T. (Chem. Rev., 1996)
And see references therein.

(untitled) - Eisenberger, P.; Gischig, S.; Togni, A. (Chem.–Eur. J., 2006)

(untitled) - Kieltsch, I.; Eisenberger, P.; Togni, A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Shibata, N.; Matsnev, A.; Cahard, D. (Beilstein J. Org. Chem., 2010)

(untitled) - Yasu, Y.; Koike, T.; Akita, M. (Angew. Chem., Int. Ed., 2012)

(untitled) - Yasu, Y.; Koike, T.; Akita, M. (Chem. Commun., 2013)

(untitled) - Yasu, Y.; Koike, T.; Akita, M. (Org. Lett., 2013)

(untitled) - Koike, T.; Akita, M. (Synlett, 2013)

(untitled) - Yasu, Y.; Arai, Y.; Tomita, R.; Koike, T.; Akita, M. (Org. Lett., 2014)

(untitled) - Rivkin, A.; Chou, T.-C.; Danishefsky, S. J. (Angew. Chem., Int. Ed., 2005)

(untitled) - Shimizu, M.; Takeda, Y.; Higashi, M.; Hiyama, T. (Angew. Chem., Int. Ed., 2009)

(untitled) - Shimizu, M.; Takeda, Y.; Higashi, M.; Hiyama, T. (Chem.–Asian J., 2011)

(untitled) - Shi, Z.; Davies, J.; Jang, S.-H.; Kaminsky, W.; Jen, A. K.-Y. (Chem. Commun., 2012)

(untitled) - Kimura, M.; Yamazaki, T.; Kitazume, T.; Kubota, T. (Org. Lett., 2004)

(untitled) - Konno, T.; Takehana, T.; Mishima, M.; Ishihara, T. (J. Org. Chem., 2006)

(untitled) - Takeda, Y.; Shimizu, M.; Hiyama, T. (Angew. Chem., Int. Ed., 2007)

(untitled) - Shimizu, M.; Takeda, Y.; Hiyama, T. (Bull. Chem. Soc. Jpn., 2011)

(untitled) - Prakash, G. K. S.; Krishnan, H. S.; Jog, P. V.; Iyer, A. P.; Olah, G. A. (Org. Lett., 2012)

(untitled) - Omote, M.; Tanaka, M.; Ikeda, A.; Nomura, S.; Tarui, A.; Sato, K.; Ando, A. (Org. Lett., 2012)

(untitled) - Debien, L.; Quiclet-Sire, B.; Zard, S. S. (Org. Lett., 2012)

(untitled) - Zine, K.; Petrignet, J.; Thibonnet, J.; Abarbri, M. (Synlett, 2012)

(untitled) - Aikawa, K.; Shimizu, N.; Honda, K.; Hioki, Y.; Mikami, K. (Chem. Sci., 2014)

(untitled) - Duan, J.; Dolbier, W. R., Jr; Chen, Q.-Y. (J. Org. Chem., 1998)

(untitled) - Hafner, A.; Bräse, S. (Adv. Synth. Catal., 2011)

(untitled) - Cho, E. J.; Buchwald, S. L. (Org. Lett., 2011)

(untitled) - Parsons, A. T.; Senecal, T. D.; Buchwald, S. L. (Angew. Chem., Int. Ed., 2012)

(untitled) - He, Z.; Luo, T.; Hu, M.; Cao, Y.; Hu, J. (Angew. Chem., Int. Ed., 2012)

(untitled) - Li, Y.; Wu, L.; Neumann, H.; Beller, M. (Chem. Commun., 2013)

(untitled) - Li, Z.; Cui, Z.; Liu, Z.-Q. (Org. Lett., 2013)

(untitled) - Patra, T.; Deb, A.; Manna, S.; Sharma, U.; Maiti, D. (Eur. J. Org. Chem., 2013)

(untitled) - Janson, P. G.; Ghoneim, I.; Ilchenko, N. O.; Szabó, K. J. (Org. Lett., 2012)

(untitled) - Iqbal, N.; Jung, J.; Park, S.; Cho, E. J. (Angew. Chem., Int. Ed., 2014)

(untitled) - Feng, C.; Loh, T.-P. (Chem. Sci., 2012)

(untitled) - Egami, H.; Shimizu, R.; Sodeoka, M. (Tetrahedron Lett., 2012)

(untitled) - Feng, C.; Loh, T.-P. (Angew. Chem., Int. Ed., 2013)

(untitled) - Wang, X.-P.; Lin, J.-H.; Zhang, C.-P.; Xiao, J.-C.; Zheng, X. (Beilstein J. Org. Chem., 2013)

(untitled) - Besset, T.; Cahard, D.; Pannecoucke, X. (J. Org. Chem., 2014)

(untitled) - Iqbal, N.; Choi, S.; Kim, E.; Cho, E. J. (J. Org. Chem., 2012)

(untitled) - Németh, G.; Kapiller-Dezsofi, R.; Lax, G.; Simig, G. (Tetrahedron, 1996)

(untitled) - Liu, X.; Shimizu, M.; Hiyama, T. (Angew. Chem., Int. Ed., 2004)
And see references for the bioactivity therein.